Perspektif Kaum Feminis Tentang Ekologi Holistik - Jewadut, Jean Loustar; Denar, Benediktus (Jurnal Alternatif Wacana Ilmiah Interkultural, 2024)
This article aims to explain the feminist perspective on holistic ecology which originates from the wisdom of local communities. The wisdom of local communities provides inspiration for feminists to position nature as a friend that must be respected and preserved. This article was written using qualitative methods with a literature study approach. With this method, researchers collect and analyze data obtained from various sources such as articles, books, documents, newspapers, policies, and various results of previous research or studies. The results of this research show that a feminist perspective that connects women's suffering with the suffering of the earth can contribute to the movement to fight for gender justice and ecological justice. Apart from that, feminist ideas about ecology reconstruct the relational dimension in the created order which places humans and nature in a reciprocal relationship, namely that humans need nature as a resource that supports daily life and nature needs humans as wise managers. The reconstruction of the relational dimension in the created order is a form of counter idea to the tendency of modern society which only prioritizes the dimension of rationality in relations with the environment.